Managing the health of the elite athlete: a new integrated performance health management and coaching model - Dijkstra, H. P.; Pollock, N.; Chakraverty, R.; Alonso, J. M. (British Journal of Sports Medicine, 2014)
Elite athletes endeavour to train and compete even when ill or injured. Their motivation may be intrinsic or due to coach and team pressures. The sports medicine physician plays an important role to risk-manage the health of the competing athlete in partnership with the coach and other members of the support team. The sports medicine physician needs to strike the right ethical and operational balance between health management and optimising performance. It is necessary to revisit the popular delivery model of sports medicine and science services to elite athletes based on the current reductionist multispecialist system lacking in practice an integrated approach and effective communication. Athlete and coach in isolation or with a member of the multidisciplinary support team, often not qualified or experienced to do so, decide on the utilisation of services and how to apply the recommendations. We propose a new Integrated Performance Health Management and Coaching model based on the UK Athletics experience in preparation for the London Olympic and Paralympic Games. The Medical and Coaching Teams are managed by qualified and experienced individuals operating in synergy towards a common performance goal, accountable to a Performance Director and ultimately to the Board of Directors. We describe the systems, processes and implementation strategies to assist the athlete, coach and support teams to continuously monitor and manage athlete health and performance. These systems facilitate a balanced approach to training and competing decisions, especially while the athlete is ill or injured. They take into account the best medical advice and athlete preference. This Integrated Performance Health Management and Coaching model underpinned the Track and Field Gold Medal performances at the London Olympic and Paralympic Games.